SAT0525 Tocilizumab Compared with Anakinra in Refractory Adult-Onset Still's Disease. Multicenter Study of 75 Patients. (9th June 2015) - Palmou, N.; Calvo-Río, V.; Blanco, R.; Hernández, J.L.; Ortiz-Sanjuan, F.; Olivé, A.; Riveros, A.; Castañeda, S.; Narváez, F.J.; Velloso-Feijoo, M.L.; Hernández, M.V.; Sifuentes Giraldo, W.A.; et al.
Abstract : Background: Interleukin (IL)-1 and IL-6 are pivotal cytokines in the pathogenesis of adult-onset Still's disease (AOSD). Objectives: Compare the efficacy and safety of tocilizumab (TCZ) versus anakinra (ANK) given for at least 1 year to AODS patients refractory to conventional treatment. Methods: Multicenter study (31 hospitals) of 75 patients (TCZ; n=34 and ANK; n 41) with AODS refractory to conventional immunosuppressive drugs and in many cases also to other biological agents. Results: Comparisons of the group of patients with TCZ and ANK were: a) Average age: 39±16 vs. 34±14 years (p=0.2) b) Percentage of women: 76.5% vs. 63.4% (p=0.2) c) Median disease duration 4.2 [1-9] vs. 2.2 [0.3 to 4.9] years (p=0.14) d) Average dose of prednisone 15±9.9 mg/day vs. 28.3±22 mg/day (p=0.013) e) Median of conventional immunosuppressants (2 [1-3] vs 1 [1-2] (p=0.05) f) Median of other biological therapies: 1 [0-2] vs. 0 [0-1] (p=0.04). The initial dose of i.v. TCZ were: 8 mg/kg/4 weeks (n=22), 8 mg/kg/2 weeks (n=10) and 4 mg/kg/4 weeks (n=2). ANK dose was 100 mg/day s.c. Both biologic agents were often combined with a conventional immunosuppressive drug (55.9% vs 70.7%; p=0.2). Both biologic agents yielded a quick and sustained improvement of all clinical and laboratory parameters (Table ). The improvement in the clinical parameters was similar in both groups. However an earlier improvement of CRP and ESR was observed following TCZ therapy. After a median follow-up of 19 months [12-31] with TCZ and 15.5 months [4.5 to 50] with ANK (p=0.1), the major adverse effects in the TCZ group were: elevation liver enzymes (n=4), mild to moderate leucopenia (4), upper respiratory tract infection (3), pneumonia (1), pyelonephritis and severe enterocolitis (1) and spondylodiscitis (1). In the group of ANK: skin lesions (n=8), mild leucopenia (3), myopathy (1), respiratory infection by P. aeruginosa and gluteal abscess (1), herpes zoster (1), osteomyelitis (1) and infection of urinary tract (2). While none of the TCZ-treated required discontinuation of the drug due to inefficacy, ANK had to be discontinued for this reason in 11 patients (p=0.001). Adverse effects leading to discontinuation of the drug were observed in 2 patients with TCZ and 4 patients with ANK (p=0.54). Conclusions: TCZ and ANK are associated with a rapid and sustained clinical improvement in most patients with refractory AODS. However, TCZ appears to be more effective than ANK. Disclosure of Interest: None declared